A benchmark ab initio study of the complex potential energy surfaces of the OH- + CH3CH2Y [Y = F, Cl, Br, I] reactions - Tasi Domonkos Attilaó; Tokaji Csenge; Czakó Gábor (2021)
We provide the first benchmark characterization of the OH- + CH3CH2Y [Y = F, Cl, Br, I] reactions utilizing the high-level explicitly-correlated CCSD(T)-F12b method with the aug-cc-pVnZ [n = 2(D), 3(T), 4(Q)] basis sets. We explore and analyze the stationary points of the elimination (E2) and substitution (S(N)2) reactions, including anti-E2, syn-E2, back-side attack, front-side attack, and double inversion. In all cases, S(N)2 is thermodynamically more preferred than E2. In the entrance channel of S(N)2 a significant front-side complex formation is revealed, and in the product channel the global minimum of the title reactions is obtained at the hydrogen-bonded CH3CH2OHMIDLINE HORIZONTAL ELLIPSISY- complex. Similar to the OH- + CH3Y reactions, double inversion can proceed via a notably lower-energy pathway than front-side attack, moreover, for Y = I double inversion becomes barrier-less. For the transition state of the anti-E2, a prominent ZPE effect emerges, giving an opportunity for a kinetically more favored pathway than back-side attack. In addition to S(N)2 and E2, other possible product channels are considered, and in most cases, the benchmark reaction enthalpies are in excellent agreement with the experimental data.
Keywords: Kémiai tudományok